问题
解答题
|
答案
(1)
÷9 10
+7 4
×3 7 9 10
=
×9 10
+4 7
×3 7 9 10
=
×(9 10
+4 7
)3 7
=
;9 10
(2)(
-14 15
-5 9
)×451 5
=
×45-14 15
×45-5 9
×451 5
=42-25-9
=17-9
=8;
(3)
+6 7
×7 9
+3 2 5 6
=
+6 7
+7 6 5 6
=
+(6 7
+7 6
)5 6
=
+26 7
=2
;6 7
(4)3÷
-3 5
÷33 5
=5-1 5
=4
;4 5
(5)6÷
÷1 5
÷53 5
=30÷
÷53 5
=50÷5
=10;
(6)[
-(5 6
+2 5
)]×1 3 5 7
=[
-5 6
]×11 15 5 7
=
×1 10 5 7
=
;1 14
(7)
×5 11
÷1 2
×5 11 1 2
=(
÷5 11
)×(5 11
×1 2
)1 2
=1×1 4
=
;1 4
(8)
÷8+3 4
÷3 4 8 7
=
×3 4
+1 8
×3 4 7 8
=
×(3 4
+1 8
)7 8
=
;3 4
(9)
×8 15
-7 9
×7 15 7 9
=(
-8 15
)×7 15 7 9
=
×1 15 7 9
=
.7 135